2012
DOI: 10.1038/ajg.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Genetics of Barrett's: The Bigger, the Better

Abstract: : Barrett ' s esophagus (BE) is a common lesion that predisposes to a highly fatal esophageal adenocarcinoma (EA). There is evidence that BE or parts of its phenotype are genetically predisposed. Several single-nucleotide polymorphisms (SNPs) have been validated as predisposing to BE but the inherent fl aws in the trial sizes, presence of controls and statistical power need circumspect analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The probability to find one single specific biomarker providing all diagnostic, predictive, and prognostic significance in GERD, BE, and/or EAC is rather utopian, and a panel of biomarkers maybe will solve this problem [81, 123, 124]. Upcoming new technologies such as RNA and DNA microarrays, epigenetics, and proteomics in association with bioinformatics give hope to find novel and reliable biomarkers in gastrointestinal tumors and especially for prognosis and prediction of BE and EAC [114].…”
Section: Approach and Outlookmentioning
confidence: 99%
“…The probability to find one single specific biomarker providing all diagnostic, predictive, and prognostic significance in GERD, BE, and/or EAC is rather utopian, and a panel of biomarkers maybe will solve this problem [81, 123, 124]. Upcoming new technologies such as RNA and DNA microarrays, epigenetics, and proteomics in association with bioinformatics give hope to find novel and reliable biomarkers in gastrointestinal tumors and especially for prognosis and prediction of BE and EAC [114].…”
Section: Approach and Outlookmentioning
confidence: 99%
“…8 One study demonstrated basal acid output increased by a median of 96 per cent two days after ranitidine therapy ceased (p<0.01), which returned to pretreatment values by day 10 in healthy volunteers. 9 Other evidence points to a more prolonged effect with longer exposure -at least two months after a two-month treatment course. 8 Data is relatively conflicting with regards to the exact clinical consequences RAHS has from PPIs.…”
Section: Rebound Acid Hypersecretionmentioning
confidence: 99%